Early Cretaceous–Late Miocene Basin–Mountains Pattern in the Northeastern Margin of the Tibetan Plateau, NW China: Evidence From Detrital Zircon Chronology in the Lanzhou Basin - Liu, Hang; Gong, Hu–jun; Luo, Fen–hong; Zhang, Rui (Geological journal (Chichester, England), 2025)
The basin‐mountain tectonic system along the northeastern margin of the Tibetan Plateau represents a structural signature formed through Cenozoic collision between the Indian and Eurasian plates and subsequent tectonic adjustments, though the mechanisms controlling its tectonic deformation and uplift remain subjects of ongoing scientific debate. The Cenozoic sedimentary sequences preserved in the Lanzhou Basin provide critical archives documenting both provenance variations and tectonic evolution of adjacent orogenic belts. In this study, we employed detrital zircon U–Pb geochronology combined with bulk sediment geochemical analysis (major and trace elements) to reconstruct source‐to‐sink relationships. Quantitative provenance discrimination was achieved through DZmix and DZstats modelling to determine relative contributions from potential source terrains. Analysis of the modelling results showed that During the Early Cretaceous and Late Palaeocene, the Indo‐Eurasian collision affected the West Qinling (50.3% contribution) and North Qilian (34.6%) orogen belts. A significant provenance shift occurred during the Eocene when large‐scale planation surfaces developed across the northeastern Tibetan Plateau margin, resulting in complete cessation of West Qinling‐derived sediments (3% contribution) to the Lanzhou Basin. Subsequent Early Oligocene stratigraphic records indicate resurgent West Qinling input (31%), marking its secondary uplift phase. Multiphase uplift‐denudation cycles characterised both Qilian and West Qinling domains throughout the Early Cretaceous to Late Miocene. Notably, spatiotemporal disparities emerged between North and South Qilian uplift histories, with differential exhumation timing and sediment routing generating distinct provenance signatures in basin fills.